2020
DOI: 10.1111/ecot.12242
|View full text |Cite
|
Sign up to set email alerts
|

Wage premium in the state sector and state‐owned enterprises: Econometric evidence from a transition country in times of austerity

Abstract: This paper investigates the differences in the wage premium and compliance with the wage cut introduced in Serbia at the end of 2014, between two subsectors of the public sector: the state sector and state-owned enterprises. Results show that before the austerity measures were introduced, the conditional wage premium was, on average, higher in state-owned enterprises than in the state sector, with significant differences from the median to the top of the wage distribution. After the austerity measures were int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Recent evidence for Serbia has suggested that, following the 2015 wage cut, the publicsector wage premium dropped more in the state sector than in state-owned enterprises (Vladisavljević & Nojković, 2018). The lower compliance of state-owned enterprises (vs. the state sector) may be explained by their reduced fiscal discipline and inefficient spending, together with their access to revenues that can partially finance wages (IMF, 2015).…”
Section: The Effects Of Austerity Measures On the Gender Pay Gapmentioning
confidence: 99%
“…Recent evidence for Serbia has suggested that, following the 2015 wage cut, the publicsector wage premium dropped more in the state sector than in state-owned enterprises (Vladisavljević & Nojković, 2018). The lower compliance of state-owned enterprises (vs. the state sector) may be explained by their reduced fiscal discipline and inefficient spending, together with their access to revenues that can partially finance wages (IMF, 2015).…”
Section: The Effects Of Austerity Measures On the Gender Pay Gapmentioning
confidence: 99%